Study guides

☆☆

Q: How do you solve it 5x plus 8x plus 3x - 2x?

Write your answer...

Submit

Related questions

It is: 8-2x

3x + 2x = 5x. 5x= (-4) X = (-4)/5 x= -0.8

2x + 3x = 5x.

2x + 3x = 5x

3x + 2x = 5x

No. 3x plus 2x = 5x. 3x multiplied by 2x = 6x²

2x+3x = 5x

5x+2 = 3x-6 5x-3x = -6-2 2x = -8 x = -4

3x + 4 = 5x - 6 -3x -3x 4 = 2x - 6 +6 +6 10 = 2x 5 = x

5x+(6-3x)+8=5x+6-3x+8=2x+14 2x + 14

5x

3x+5=4-2x+6 5x=4-1 5x=3 x=3/5

3x+4 = 5x-6 3x-5x = -6-4 -2x = -10 x = 5

3x + 5x = 2x + 28x = 2x + 26x = 2x = (2/6) = 1/3

5x+7 = 2x-3 5x-2x = -3-7 3x = -10 x = -10/3

5x + 4 - 3x + 5 + 2x - 9 = 4x

3x-4=5x+6 gives: 2x=-10 which gives x=-5

2x + 3x + 6 = 5x + 6

2x+3x-2=0=5x=0+2=5x=2=5x_5=2_5=x=0.4

5x+7=3x-21 -7= -7 5x=3x-14 -3x=-3x 2x=-14 2x/2x=2x/-14 x=-7 The Answer Is -7 -

2x + 4y - 5x + 3y = 7y - 3x

5x That's all you can get from that. If you need to solve for x you are missing part of the question

5x+7

5x-2 = 3x-6 5x = 3x - 6 +2 5x = 3x - 4 5x - 3x = -4 2x = -4 x = -2

5x - 8a + 4a - 2x + a = 3x - 3a

People also asked